2014
DOI: 10.1021/es504045g
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Ecotoxicology: Migratory Arctic Seabirds Are Exposed to Mercury Contamination While Overwintering in the Northwest Atlantic

Abstract: Arctic organisms are exposed to various levels of pollutants, among which mercury (Hg) has raised important environmental concerns. Previous studies examining Hg levels, trends, and effects on Arctic marine top predators have focused on the Arctic region. However, many of these top predators, such as seabirds, migrate to spend a large part of their life cycle far from the Arctic in areas where their exposure to contaminants is largely unknown. By combining biotelemetry and Hg and stable isotope analyses, we st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 53 publications
7
82
1
Order By: Relevance
“…The authors therefore argued that high–trophic level organisms thus also may be exposed to different levels of dietary Hg during different seasons. Fort et al also showed that little auks were more contaminated with Hg when outside the Arctic breeding area/season. As mentioned, the concentrations of total Hg in the birds of the present study changed with season (Table and Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…The authors therefore argued that high–trophic level organisms thus also may be exposed to different levels of dietary Hg during different seasons. Fort et al also showed that little auks were more contaminated with Hg when outside the Arctic breeding area/season. As mentioned, the concentrations of total Hg in the birds of the present study changed with season (Table and Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…While Phillip Island penguins exhibited larger body burdens of non-essential trace elements than penguins at Notch Island, they differed significantly from those at St Kilda and might provide a rare opportunity to investigate demographic or behavioural effects of contamination. Demographic effects of chronic exposure to contaminants in seabirds can be measured by population growth rates, survival rates and long-term breeding performance (Tartu et al, 2013;Fort et al, 2014;Goutte et al, 2014aGoutte et al, , 2014b. While the St Kilda and Phillip Island colonies are regularly surveyed and many penguins have passive induction transponders , therefore enabling mark-recapture data collection, the differences in nesting (rock crevasses at St Kilda, burrows at Phillip Island) confound a direct comparison of these measures.…”
Section: Suitability Of the Little Penguin As A Bioindicator For Locamentioning
confidence: 99%
“…the taking of a small sample of blood (<2 mL) from a free-ranging bird without sacrificing it (Becker, 2003). The success of non-lethal blood sampling techniques is evident in the literature (EaglesSmith et al, 2008;Carvalho et al, 2013;Fort et al, 2014). Trace element concentrations in avian blood reflect current dietary exposure and often correlate strongly with those in internal tissues, presenting a potentially more suitable non-lethal matrix than feathers for investigating a biologically relevant contaminant load (Monteiro and Furness, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Migratory animals can transport contaminants long distances (Blais et al 2005), and exposure to contaminants and other stressors on the nonbreeding grounds can affect subsequent life history stages (Harrison et al 2011;Fort et al 2014;Fairhurst et al 2015). Arctic wildlife that spend considerable portions of their annual cycle in more urbanized areas could therefore be important vectors for Hg to Arctic regions (Lewis et al 1993;Gochfeld 1997;Burger andElbin 2015a, 2015b), and the Hg they acquire during the winter could influence individuals on their Arctic breeding grounds (Fort et al 2014;Lavoie et al 2014).…”
Section: Introductionmentioning
confidence: 99%